2011
DOI: 10.3892/etm.2011.406
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of diethylnitrosamine-induced liver carcinogenesis in Syrian golden hamsters

Abstract: The aim of this study was to characterize hepato carcinogenesis in diethylnitrosamine (DEN)-treated hamsters. Syrian golden hamsters (n=36) were administered DEN by hypodermic injection and addition to drinking water. Morphological analyses, including light microscopy and immunohistochemistry of α-fetal protein (AFP), were performed on liver and lung tissues. Primary cell culture and tumor transplantation were carried out to evaluate the potential application in hepatocellular carcinoma (HCC) research. From 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…29,34 The DEN rats also showed significant increase in AFP level compared to control animals. This result is in line with previous studies 35,36 that indicated that increase in serum AFP level upon DEN induction is associated with increase in tumor growth.…”
Section: Discussionsupporting
confidence: 93%
“…29,34 The DEN rats also showed significant increase in AFP level compared to control animals. This result is in line with previous studies 35,36 that indicated that increase in serum AFP level upon DEN induction is associated with increase in tumor growth.…”
Section: Discussionsupporting
confidence: 93%
“…The increasing number of transformed hepatocytes were significantly higher in DEN treated group compared to mice given 0.2% curcuminoids diet and saline injection as well as compared to basal saline group (p<0.05). Development of liver carcinogenesis induced by DEN injection is depending on the duration, dose and administration route [8][9]15,17,[19][20][21]. Our result showed that treatment with 0.2% curcuminoids in diet can prevent the liver carcinogenesis proven by lower number of transformed hepatocytes in a group treated with curcuminoids after DEN injection compared with Basal DEN ( Figure 5).…”
Section: Resultsmentioning
confidence: 67%
“…It has been postulated that the necrotic hepatocytes will release their cellular constituents into the surrounding interstitial tissue which lead to inflammatory infiltration [22]. The administration of DEN, showed central veins surrounded by extensive necrosis and inflammatory infiltration, clusters of necrotic hepatocytes, bile duct proliferation and marked atypia, also caused inflammatory cell infiltrates, fatty degeneration, hyperplastic nodules and biliary cysts [19,21]. Transformed hepatocytes were characterized with pleomorphic, enlargement and hyperchromatin nuclei make greater nuclear per cytoplasmic ratio (N/C ratio), and centrally prominent nucleoli.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present study suggest that CASE impedes DEN-induced hepatocarcinogenesis in rats via suppressing GST-P1 expression and modulating upstream (TGF-β 1 , TβRI and TβRII) and downstream (Imp7 and Imp8) mediators of the TGF-β/Smad signaling pathway. Non-viral and non-alcohol-associated hepatocarcinogenesis, including DEN-induced hepatocarcinogenesis, typically progresses from chronic inflammation through fibrosis and cirrhosis, finally becoming hepatocarcinogenesis ( 15 ). A number of studies have acknowledged the link between chronic liver inflammation and hepatocarcinogenesis, particularly HCC ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%